Analysis on traveling time of Internet - LI Chao; ZHAO Hai; ZHANG Xin; YUAN Shao-qian (Tongxin xuebao)
Based on the giant data samples authorized by CAIDA,it found that the Internet traveling time was typically distributed by multi-modal and heavy-tailed when the Internet traveling time was statistically analyzed.Furthermore,a research on the relationship between the traveling diameter and the traveling time from the whole and local data samples supposed that link delay was the leading cause for the great variance of the traveling time,and a revising algorithm was proposed to process the raw data samples to obtain link delay.The statistical analysis of link delay presented that the ratio of the biggest link delay to the traveling time in more than 90% of paths was over 1/4.Then a definition of dominant delay was put forward.The traveling time is affected greatly by dominant delay,which makes the similar diameter’s traveling time distinct.